Language, texts, and society : explorations in ancient Indian culture and religion - Olivelle, Patrick (Cultural, historical and textual studies of religions., 2011)
This collection brings together the research papers of Patrick Olivelle, published over a period of about ten years. The unifying theme of these studies is the search for historical context and developments hidden within words and texts.